Effects of low-level laser therapy on distraction osteogenesis: a histological analysis (Revista da Faculdade de Odontologia - UPF, 2013)
Objective: The aim of this study was to assess the effect of low-level laser therapy on tissue repair in the rabbit mandible after osteotomy and distraction osteogenesis, through histological analysis of the area of bone neo formation and measurement of the amount of neoformed bone. Methods: Twenty-four male New Zealand white rabbits were randomly allocated into one of two groups: experiment (laser applied directly over the site of fracture and distraction osteogenesis) or control (non-irradiated animals). Distraction osteogenesis was performed according to the following protocol: 3 days of latency, 7 days of activation (0.8 mm/day), and 10 days of consolidation. In the experiment group, irradiation was performed with an infrared laser (AlGaAs; wave-length 830 nm, CW, time 101 seconds, 40mW), at a dose of 10 J/cm2 per session, every 48 hours during the activation period. Twenty days after surgery, all rabbits were sacrificed. Results: The amount of neoformed bone was significantly higher in the laser-treated group (62.68%) than in the control group (43.09%) (p < 0.001). Conclusion: The application of low-level laser therapy following the irradiation protocol used in this study had a positive effect on the tissue repair process in a rabbit model of mandibular fracture and distraction osteogenesis, as shown by histological analysis.